The Correlation between the Utilization of M3 Board Learning Media and Students’ Learning Outcomes - Maria Gaudensia Luruk; Justin Eduardo Simarmata; Kondradus Yohanes Klau (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2025)
This study aims to determine the correlation between the utilization of M3 board learning media and students’ learning outcomes on the topic of measures of central tendency. This research employed a quantitative approach with a correlational design using the Pearson Product Moment method. The population consisted of two eighth-grade classes with a total of 34 students at SMP Swasta 17 Agustus Webalu, while the sample was class VIII A consisting of 15 students. Data were collected through a questionnaire to measure the utilization of M3 board learning media and a test to assess students’ learning outcomes. The validity test results showed that all 12 questionnaire items were valid, with  , and the reliability test yielded a Cronbach’s Alpha value of 0.776 (> 0.6), indicating that the instrument was reliable. The normality test indicated a significance value of 0.248 (> 0.05), confirming that the data were normally distributed. Pearson correlation analysis revealed a correlation coefficient of 0.2646, categorized as low, and 0.8591, categorized as very strong, indicating a positive correlation between the utilization of M3 board learning media and students’ learning outcomes.